GREEN INNOVATION AND FINANCIAL PERFORMANCE ON COMPANY VALUE - Ardhelia Shafa Hanindita; Ririh Dian Pratiwi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Sustainable waste management and corporate financial performance have a mutually supportive relationship, where effective waste management practices can have a positive impact on financial performance. This study aims to examine the effect of green innovation and financial performance on corporate value, as measured by the Tobin's Q ratio and Price to Book Value. The independent variables analyzed include ROA, dividend yield, and debt to equity ratio, with company size as a control variable. This study focuses on food and beverage companies listed on the Indonesia Stock Exchange in the period 2018 to 2022, using secondary data obtained from annual financial reports and corporate sustainability reports. Purposive sampling technique was used to select samples, and data were analyzed using SPSS version 26. The results showed that green innovation did not affect Tobin's Q and Price to Book Value, ROA also had no effect on both ratios, while dividend yield affects Tobin's Q and Price to Book Value, and debt to equity ratio had no impact on both ratios.